EDUCATIONAL TECHNOLOGIES FOR THE SELF-CARE OF CHILDREN WITH SICKLE CELL ANEMIA: AN INTEGRATIVE REVIEW - Santana, Raquel Castro; Silva, Liliane Faria da; Gama, Priscila da Silva Miranda da; Nascimento, Luciana de Cássia Nunes; Silveira, Ana Luiza Dorneles da; Moraes, Juliana Rezende Montenegro Medeiros de (Cogitare Enfermagem, 2024)
Objective: To identify the educational technologies used to help children with sickle cell anemia in their self-care. Method: an integrative review carried out in six consecutive phases, between June and July 2023, with no time frame, in the following information resources: Public/published Medline, Virtual Health Library, Scientific Electronic Library Onl ine, and Web of Science and Cumulative Index to Nursing and Allied Health Literature. Results: Five studies were found, of which the following stood out: a game, two electronic applications, a coloring book, and a guided image for pain relief. All the educational technologies reflect the child's better understanding of self-care. Conclusion: The selected studies allowed us to understand that educational technologies help children with sickle cell anemia to understand the disease and take actions that improve its signs and symptoms, favoring self-care, but it is essential to create new educational technologies since most of the findings are old and do not match the current reality.